A Systematic Review and Quality Assessment of Clinical Practice Nursing Guidelines for Ostomy Care - Hutton, Megan; Prins, Heather; Yuan, Yuhong; Solitano, Virginia; Radford , Shellie; Vuyyuru, Sudheer Kumar; Abushamma, Suha; Rieder, Florian; Jairath, Vipul (Canadian Journal of Wound, Ostomy and Continence, 2025)
Background: People living with an intestinal stoma require specialized interdisciplinary care throughout their surgical journey and beyond. We evaluated nursing guidelines focused on the clinical management of people living with intestinal ostomies, identified knowledge and system gaps, and supported the development of evidence-based patient care pathways. Methods: A systematic literature search was conducted across MEDLINE, Embase, and major nursing organization websites up to March 25, 2024, to identify evidence-based practical guidelines developed by nursing organizations for caring for patients with intestinal stomas post-ostomy formation. We summarized the evidence and critically appraised it using the AGREE II instrument. Results: Fourteen nursing guidelines met the inclusion criteria, from Australia, Canada, Italy, the UK, the USA, and three international working groups, ranging from 2013 to 2023. These guidelines offer extensive coverage of ostomy care topics and provide valuable first-line care experience and consensus statements, particularly for postoperative stoma and peristomal care. In the AGREE II assessment, most guidelines were rated as moderate quality (scores <6), with recommended modifications primarily in the rigor of development and applicability. Conclusions: Critical appraisal of clinical practice nursing guidelines for ostomy care highlights both strengths and areas for improvement and expansion within existing guidelines. These insights are essential for non-nursing healthcare providers and contribute to the development of patient care pathways for individuals with Crohn’s disease and permanent ileostomies.